Potential of Anticoagulan Garlic Estract (Allium sativum) Using Lee-White Method and Blood Destruction - Rahmawati Rahmawati; Muammar Fawwas; Rais Razak; Utami Islamiati (Majalah Farmaseutik, 2018)
Garlic (Allium sativum L.) contains essential oils, allicin compounds, alliin and other organosulfur compounds such as ajoene which play a role in anticoagulants. This study aimed to examine the anticoagulant activity of garlic extract using the Lee-White method and blood smear. Anticoagulant activity testing was carried out by looking at the time it took for the blood to freeze after adding garlic juice, 96% ethanol (negative control) and EDTA (positive control) and looking at the red blood cell profile under a microscope (blood smear). From the test results showed that garlic extract had anticoagulant activity in which the Lee-White method, blood control freezing for three consecutive probes occurred at 4 minutes, 3 minutes 30 seconds and 3 minutes 30 seconds; addition of 96% ethanol occurred at 4 minutes 30 seconds, 2 minutes 30 seconds and 2 minutes 30 seconds and the addition of EDTA and garlic extract did not experience blood clots. Then in the blood smear method, the red blood cells added with garlic juice look round and not in groups.